An ampyrone based azo dye as pH-responsive and chemo-reversible colorimetric fluorescent probe for Al3+ in semi-aqueous medium: implication towards logic gate analysis. (18th January 2018) - Bartwal, Gaurav; Aggarwal, Komal; Khurana, Jitender M.
Abstract : A novel ampyrone based azo dye, 4-((6-hydroxybenzo[ d ][1, 3]dioxol-5-yl)diazenyl)-1, 5-dimethyl-2-phenyl-1 H -pyrazol-3(2 H )-one (1 ), was synthesized by coupling sesamol and 4-amino antipyrine (ampyrone). Abstract : A novel ampyrone based azo dye, 4-((6-hydroxybenzo[ d ][1, 3]dioxol-5-yl)diazenyl)-1, 5-dimethyl-2-phenyl-1 H -pyrazol-3(2 H )-one (1 ), was synthesized by coupling sesamol and 4-amino antipyrine (ampyrone) and was characterized spectroscopically. The interaction of azo dye (1 ) with different metal ions was studied using UV-vis and fluorescence spectra. Chemosensor1 exhibits high selectivity and sensitivity towards Al 3+ over other metal ions by fluorescence enhancement in methanol : water (1 : 1, v/v, at pH = 7.2), which could also be detected directly by the naked eye under visible light. The fluorescence of the1 –Al 3+ complex was found to be reversible in the presence of EDTA. The pH-dependent absorption behavior of chemosensor1 was also investigated. It was observed that chemosensor1 could also be used as a selective 'naked-eye' colorimetric sensor for H + and displayed a very strong red shift in the absorption band from 492 nm to 540 nm with a notable color change from yellow to violet-blue. Moreover, chemosensor1 showed keto–enol tautomerization in the presence of acidic media and both forms were confirmed by 1 H and 13 C NMR spectra. Practical applicability of sensor1 was further explored using sensing strip analysis, which enables rapid detection of Al 3+ and H + ions. NMR and DFT optimized geometries of chemosensor1 suggest that the compound is present in the azo form (enol form) in the ground state. In addition, an INHIBIT logic gate was constructed based on the multi-responsive properties of chemosensor1 induced by Al 3+ and EDTA 2−, which contained two input signals (In1: Al 3+, In2: EDTA) and an output signal (O1: fluorescence intensity at 613 nm). The chemosensor1 exhibited a high association constant with a detection limit of 3.55 × 10 −7 M for Al 3+ in MeOH–water solution.